Analyzing Government Spending and Consumers’ Welfare in Nigeria: An Auto-Regressive Distributed Lag Approach (ARDL) - Song, Muru Bitrus (Penerbit Hellow Pustaka, 2025)
Abstract Nigerian government spending on recurrent expenditures, particularly on financial intervention programmes, has increased during the past eight years. Despite this, the country is still recognized as a poor nation with a high percentage of poverty in Sub-Sahara Africa. Therefore, the study examined the effect of government spending on consumers’ welfare from 1986 to 2023. The reason for the timeframe was due to the adoption ARDL approach. The study used secondary data that was collected from Central Bank of Nigeria, Statistical Bulletin (2023), as well as, International Monetary Fund data base (2025). Augmented Dickey Fuller (ADF) and Philip Perron (PP) unit root test were used for the pretest; while Auto-regressive Distributed Lag was used to achieved the formulated objectives. Both the ADF and PP confirmed that lending interest rate was stationary at level; while, private consumption expenditure, recurrent expenditure, capital expenditure, and consumer price index were stationary at first level difference. The bound test confirmed a long-run association between the variables. The ARDL result showed that recurrent expenditure and lending interest rate were significantly and positively related to private consumption expenditure, whereas consumer price index was significantly and negatively related to it. Furthermore, capital expenditure was insignificant. It was concluded that recurrent expenditure was the only means through which Nigerian government boosts consumers’ welfare in term of spending, while maintaining lower lending rates and consumer price index support consumers’ welfare. Therefore, the study recommended that governments at the federal, state, and local levels should increase their capital expenditure through huge investments in infrastructure and other capital projects.